Efeito de fontes e doses de fósforo na adubação da soja (Glycine max (L) Merril), em um solo sob campo cerrado - Pereira, João; Braga, José Mário; Ferreira de Novais, Roberto (Revista Ceres, 2025)
This work has the objetives to study the effect of six sources of phosphorus: (ordinary superphosphate, triples super phosphate, bone meal, Araxá rock phosphate, thermo phosphate and Thomas slag) on the absorption of P, N, Ca, Mg and K and nodulation of soybeans, Mineira vir, when applied broadcast at three rates (0,50 and 100 kg of P205/ha). The experimenta was installed on a medium textural dark latossol which developed under a "Campo-Cerrado" vegetation.